Pengembangan Media Lift The Flap Book Untuk Mengenalkan Perilaku Hidup Bersih Dan Sehat Pada Anak Usia Dini: Studi Validasi Model Addie - Fatimah; Rahmi Sofyan; Rahmatun Nessa (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The implementation of Clean and Healthy Living Behaviors (PHBS) is very important for early childhood. In teaching, the conventional lecture method without interaction media causes the understanding of children aged 5-6 years to be less optimal. The ADDIE model Research and Development (R&D) research aims to develop the media lift the flap book